The Opinions of Linguists and Exegetes on the denotation of Affirmation and Negation of the Root ( جنح) in the Holy Quran - Dr. Majid Kamel Hussein Al-Badri (Journal of College of Education, 2026)
The term( جنح ) and its derivatives occur in various contexts within the Holy Quran. This research explores the views of linguists and Quranic exegetes concerning the denotation of affirmation and negation associated with the linguistic root ( جنح) in the Quranic text. The study seeks to explain these perspectives and examine the tools employed in their interpretations. Furthermore, it aims to contribute a renewed vision in the analysis of Quranic vocabulary. The study is organized into three main sections, preceded by an introduction and followed by a conclusion. The introduction provides a linguistic analysis of the root ( جنح). The first section investigates the affirmative usage of ( جنح) in the Quran. The second section addresses the implications of negation in the construct of the tool (لا ) (لا جناح ). The third section examines the implications of negation in the construct of the modal verb ( ليس ) (ليس عليكم جناح) The conclusion summarizes the most important findings of the research. I use some linguistics , exegetes and other relevant references